CARDIOVASCULAR RISK FACTORS IN TYPE 1 DIABETES MELLITUS: ANY DIFFERENCE BETWEEN ADOLESCENTS AND YOUNG ADULTS FOR SUBCLINICAL ATHEROSCLEROSIS?. (June 2022) - Bortolotti, Stefano; Cattazzo, Filippo; Tagetti, Angela; Marcon, Denise; Rosin, Elena; Minuz, Pietro; Maffeis, Claudio; Fava, Cristiano
Abstract : Objective: Atherosclerosis is one of the most dangerous complications of type 1 diabetes mellitus (T1DM) leading to cardiovascular (CV) diseases. There are only a few data about the relative burden of the other CV risk factors apart from DM in determining subclinical atherosclerosis at different ages in patients with T1DM. Thus, the aim of the present study was to compare adolescents and young adults with T1DM about the association of the different CV risk factors with subclinical vascular damage. Design and method: In sixty children and sixty adults with T1DM matched for sex and glycated haemoglobin [HbA1c] level, carotid intima-media thickness (cIMT), carotid coefficient of distensibility (cDC) and Pulse Wave Velocity (PWV) were measured by carotid ultrasonography and the SphygmoCor XCel device. Peripheral and central systolic/diastolic blood pressure (pSBP/pDBP; cSBP/cDBP), body mass index (BMI), HbA1c, nonHDL/HDL-cholesterol ratio were also analyzed. Demographic and hemodynamic variables are shown in Table-1. The relationship between risk factors and markers of subclinical vascular damage was assessed in each group by linear regression models using as covariates: gender, BMI, age, HbA1c, nonHDL/HDL-cholesterol ratio, and either pBP or cBP. Results: cIMT was associated neither with hemodynamic parameters nor with metabolic risk factor in both adolescents and adults. In adolescents, cDC was associated with pSBP (±SEM -017 ± 0.09 p-value = 0.013) whereas PWV showed an association with cSBP (±SEM 0.37 ± 0.008; p-value:0.003), cDBP (±SEM 0.46 ± 0.02; p-value:0.000), pDBP (±SEM 0.35 ± 0.01; p-value:0.003), and non-HDL/HDL ratio (±SEM 0.35 ± 0.12; p-value:0.007). In young adults, cDC was associated with cDBP (±SEM -0.28 ± 0.13; p-value:0.005) and pDBP (±SEM -0.26 ± 0.15 p-value = 0.02) whereas PWV was associated with cDBP (±SEM 0.36 ± 0.009; p-value:0.02), pSBP (±SEM 0.37 ± 0.01; p-value:0.002) and pDBP (±SEM 0.37 ± 0.02; p-value: 0.004). Conclusions: Subclinical vascular damages in T1DM are associated especially with hemodynamic factors, such as SBP and DBP, both in adolescents and young adults. Our findings suggest that BP control may be paramount starting early in patients with T1DM.